Berteologi, Berkristologi, dan Berpneumatologi dengan Religiositas Orang Halmahera - Mojau, Julianus (GEMA TEOLOGIKA: Jurnal Teologi Kontekstual dan Filsafat Keilahian, 2024)
AbstractThis article is the result of research concerning the effort to dialogically bring about an encounter about the fundamental content of Christian faith in the Lord God, Jesus Christ, and the Holy Spirit as inherited by HalmaheraChristians from delegates of the Utrechtsche Zendingsvereeniging (UZV) with belief in Giki/Gikiri, Gòmánga, Jou, Ngomasa as the content of Halmahera religiosity before Islam and Christian. This effort uses the theological method of translation, anthropology, and praxis from Stephen B. Bevans by considering the soteriological meaning of the psycholinguistic meaning of the word diai in the vocabulary of three Halmahera subethnic groups (Galela, Tobelo, Loloda). Dialogical encounter is an effort to develop doing theology, Christology, and pneumatology with the religiosity of the Halmahera people which results in a new understanding of the character of the content of the Halmahera Christian faith about the Lord God in the form of diai theology, Jesus Christ in the form diai Christology, and the Holy Spirit in the form diai pneumatology which are more sensitive to structural injustice, both economic and political as well as gender and cultural-religious. AbstrakArtikel ini merupakan hasil penelitian tentang bagaimana upaya memperjumpakan secara dialogis isi iman Kristen fundamental kepada Tuhan Allah, Yesus Kristus, dan Roh Kudus sebagaimana diwarisi oleh orang-orang Kristen Halmahera dari para utusan Utrechtsche Zendingsvereeniging (UZV) dengan kepercayaan kepada Giki/Gikiri, Gòmánga, Jou, Ngomasa sebagai isi religiositas orang Halmahera sebelum Islam dan Kristen. Usaha ini  menggunakan metode berteologi terjemahan, antropologis, dan praksis dari Stephen B. Bevans dengan mempertimbangkan makna soteriologis dari makna psikolinguistik kata diai dalam kosakata tiga subetnis Halmahera (Galela, Tobelo, Loloda). Perjumpaan dialogis merupakan usaha mengembangkan berteologi, berkristologi, dan berpneumatologi dengan religiositas orang Halmahera yang menghasilkan pemahaman baru isi iman Kristen khas ke-Halmahera-an tentang Tuhan Allah dalam bentuk teologi diai, Yesus Kristus dalam bentuk kristologi diai, dan Roh Kudus dalam pneumatologi diai yang lebih peka terhadap ketidakadilan struktural, baikdalam bentuk ketidakadilan ekonomi dan politik maupun gender dan budaya-agama.